International trade and exotic pests: the risks for biodiversity and African economies - Youm, O.; Vayssières, Jean-François; Togola, A.; Robertson, S.; Nwilene, F.E. (SAGE Publications, 2011)
Trade is important for economic development and growth; however, it is also the principal means of introducing invasive pests and disease vectors that can cause environmental damage and economic losses and pose a serious risk to biodiversity. Invasive pests and trade have created a two-way linkage, leading to perceptions that African countries are becoming a source of invasive pests in other countries via trade. What phytosanitary measures do African countries have to take therefore to reduce losses in economic and trade opportunities? Another important issue is the ability of African countries to reduce trade-related pest invasions from other countries and the impact of such invasions on African economies and the environment. Management strategies that can reduce the introduction of exotic pests, while not restricting the benefits of trade or causing protective trade barriers, are desirable. This paper reviews linkages between trade and invasive pests and the resulting effects on African agricultural exports, the economy, environment and biodiversity. Strategies and policies to deal with invasive pests, trade and trade barriers and protectionism are reviewed to assess how they may affect or can be used by African countries to address these problems.